ANALISIS POLA KELUARAN PROTOTIPE SENSOR RASA PORTABLE CAMPURAN LIPID DIOCTYL PHOSPHATE DAN TRIOCTYL METHYL AMMONIUM CHLORIDE - Amalinda, Finta (Sainstek : Jurnal Sains dan Teknologi, 2016)
Portable taste sensor prototype has been fabricated as two channel ion meter and one types of ion selecting membrane. Two channel ion meter were made for pre development of the taste sensor system or as a electronic tongue wich acted as an multi channel ion meter.ion meter was made using IC op-amp LF412 as its amplifier and microcontroller Atmega8535. meanwhile types of the selecting membrane ion were made using variation: mix  of lipid diocthyl phosphate (DOP) and triocthyl methyl ammonium chloride (TOMA) with mass ratio respectively 3:7 and 9:1.  On this sensor, lipid determines membrane selectivity to particular ions. Output from taste sensor is a electric potential and then it could be compared with electrode potential references. This portable taste sensor prototype is then tested is ability to sensing for 5 types of solution: glucose, KCl, HCl, quinine, and MSG. Those 5 types represent 5 basic taste: sweet by glucose, salty by KCL, sour by HCl, bitter by quinine, and umami by MSG. Every solution is made using 1mM KCl  solution and it is variated to be 7 types of concentration. As a result, taste sensor with lipid membrane mixture of 3:7 mixing tend to respon to the anions sample, resulting potential which decreased for every increase in concentration. For membrane with a lipid mixture of 9:1 showed a tendency to respond to the cations sample, resulting potential which increased for every increase in concentration.Key words: taste sensor, ion meter, ion selecting membrane, lipid, diocthyl phosphate, methyl ammonium chloride.